Switched Bias Differential MOSFET Dosimeter - García Inza, Mariano Andrés (2014)
This paper presents a differential MOSFET sensor reading technique based on the bias controlled cycled measurement. The circuit was implemented, and tested with gamma radiation from a 60-cobalt source. Temperature rejection performance was assessed during the exposure in real-time measurements. The results show that in comparison with a single MOSFET dosimeter the thermal drift is 20 times smaller and the radiation sensitivity is approximately 10% higher. The switched biasing allows to extend the measurement range beyond MOSFET's threshold voltage saturation.